Maternal depression in Khayelitsha, South Africa: a comparison of health utilisation costs of maternal depression and the cost of intervening through a task-shifting approach - Orangi, Stacy Kwamboka (Health Economics Unit, 2017)
This study assessed the health service utilisation costs of untreated maternal depression in women early in their pregnancy in Khayelitsha, South Africa. In addition, it determined the costs of providing treatment or support to these women through a psychological intervention that was delivered by trained community health workers. This thesis was a sub-study of the AFFIRM study (Africa Focus on Intervention Research for Mental Health) whose main objective was to determine the effectiveness, acceptability, cost-effectiveness and potential sustainability of a task-shifted psychological intervention offered to depressed mothers. To determine the costs of maternal depression, health care costs were analyzed over a period of 3 months from both patient and provider perspectives; this information was obtained from participants during their first antenatal visit. These health service costs (excluding antenatal and well-baby visits) were compared between psychologically distressed pregnant women with different severity levels of depression; no depression, mild depression and moderate/severe depression. The cost of the task-shifted intervention was calculated from a provider's perspective and compared to the costs of the 'enhanced usual care' that was offered to women in the control arm. The main costs that were analyzed were the costs of screening, start-up costs, costs of the rooms and recurrent costs. Sensitivity analyses were conducted to determine the robustness of the study results. The results show that as the severity of maternal depression increases, the use of health services also increases. The health service utilisation costs among women with moderate/severe depression ($128.27 per mother/child pair per 3 month period) were almost seven times those of women who did not have depression ($19.70 per mother/child pair), amounting to a mean cost difference of $108.57. For the intervention, salaries, followed by screening costs were the major cost drivers, with screening costs amounting to $26.69 per mother screened positive. Assuming the intervention was delivered to completion without loss to follow up, the cost per mother for the intervention was $230.47 in comparison to $69.93 per mother for enhanced usual care. A sensitivity analysis showed that the screening costs were sensitive to the prevalence of maternal depression. From this study, it can be concluded that women with maternal depression use more health services and incur higher health care costs. It is possible to provide support to these women using psychological approaches that are delivered by lower level staff such as community health workers. This treatment can be affordable, depending on the budget constraints.